The ‘Fair Use' Doctrine and the Implications of Digitising for the Doctrine from a South African Perspective - Schonwetter, Tobias (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2006)
This article seeks to determine the scope of the “fair use” doctrine under South African copyright law. For these purposes, the legal requirements in the relevant international treaties for the doctrine are examined, particularly the so-called “three-step test”. Subsequently, the legal situations in other countries and regions – South Africa’s major trading partners the United States, Europe, and Australia – are described and compared. Thereafter, emphasis is placed on the impacts of digitising and the Internet on the fair use doctrine. Lastly, the article seeks possible solutions for South Africa with consideration of South Africa’s unique situation as a country between the developed and developing worlds.